Od „dna” ku „denku”. Postmodernistyczna aktualizacja dramatu M. Gorkiego - Pieczyński, Maciej (Kultury Wschodniosłowiańskie – Oblicza i Dialog, 2018)
Contemporary Russian drama is situated in a dialogue with literary and more precisely dramatic tradition. For example, this thesis clearly confirms a comedy by Igor Shpric On the bottom. The text at the level of its title refers to Maxim Gorky's play The Lower Depths. Shpric’s comedy parodies this work by presentingGorky's characters in the social and cultural context of contemporary reality. The main purpose of the paper is the intertextual analysis and interpretation of ironic Shpric’s comedy as the transcontextualization of language, poetics, themes, plot and characters ofGorky's text.